1996
DOI: 10.1007/bf02350086
|View full text |Cite
|
Sign up to set email alerts
|

The biological function of snake mobbing by Siberian chipmunks: II. Functions beneficial for the mobbers themselves

Abstract: --The functions of snake mobbing by Siberian chipmunks were studied in the context of potencial benefit to the mobbers themselves. In experiment I, the threatening effect of the mobbing was examined, and following results were obtained. The snake retreated almost always into a shelter box when it was mobbed, and the time span from the beginning of the mobbing until the completion of the snake's retreat into the box was shorter when the snake was mobbed by 2 chipmunks than when mobbed by a single one. These res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…They can discriminate between their own urine-feces and other conspecifics' ones by odor (Kobayashi and Watanabe 1986b). They can also detect faint snake scent which adhered to ground or trees after snakes crawled on them (Kobayashi 1996). Therefore, the chipmunks may obtain some information about snakes from the snake scent applied to the SSA performed chipmunk.…”
Section: Experiments 2 Response To Scent Traces On Wood Boardsmentioning
confidence: 99%
“…They can discriminate between their own urine-feces and other conspecifics' ones by odor (Kobayashi and Watanabe 1986b). They can also detect faint snake scent which adhered to ground or trees after snakes crawled on them (Kobayashi 1996). Therefore, the chipmunks may obtain some information about snakes from the snake scent applied to the SSA performed chipmunk.…”
Section: Experiments 2 Response To Scent Traces On Wood Boardsmentioning
confidence: 99%
“…It occurs in birds, primates, and other mammals. (Owings and Coss, 1977;Shields, 1984;Bartecki and Heymann, 1987;Kobayashi, 1987Kobayashi, , 1994Kobayashi, , 1996Loughry, 1988;Tamura, 1989;Heymann, 1990;Srivastava, 1991). Boesch and Boesch-Achermann (2000) reported that a party of Taï chimpanzees mobbed a leopard.…”
Section: Introductionmentioning
confidence: 96%
“…(Owings and Coss, 1977;Curio, 1978;Shields, 1984;Bartecki and Heymann, 1987;Loughry, 1988;Tamura, 1989;Isbell, 1994;Kobayashi, 1994Kobayashi, , 1996Gursky 2002a). Snake mobbing occurs in numerous primate species, including hanuman langurs (Presbytis entellus), saddle-back tamarins (Saguinus fuscicollis), Geoffroy's marmosets (Saguinus geoffroyi); white-faced capuchins (Cebus capucinus), and galago spp.…”
Section: Introductionmentioning
confidence: 97%
“…While most animals make considerable effort to avoid their predators, numerous species are known for their tendency to approach and confront their predators as a group. This behavior is known as mobbing, and was observed in fish, birds, mammals, and primates (Owings and Coss, 1977;Shields, 1984;Bartecki and Heymann, 1987;Kobayashi, 1987Kobayashi, , 1994Kobayashi, , 1996Loughry, 1988;Tamura, 1989;Heymann, 1990;Srivastava, 1991). There are numerous costs to predator mobbing.…”
mentioning
confidence: 99%